Pengaruh media audiobook cerita keberagaman sosial budaya di indonesia terhadap keterampilan menyimak peserta didik kelas V SD se-kecamatan banjarsari - Tsalitsa Ifrocha; Siti Istiyati; Septi Yulisetiani (Universitas Sebelas Maret, 2024)
The aim of this research is to examine how audiobook media stories about social diversity in Indonesia influence the listening skills of grade V students in elementary schools in Surakarta's Banjarsari District. The design of this research is experimental. Methods of data collection include tests and observations. According to the research's findings, the use of audiobook media stories of socio-cultural diversity in Indonesia impacts the listening skills of students in Banjarsari District, Surakarta's grade V elementary schools. The paired sample t-test on the hypothesis test, which examines the post-test values of the experimental and control groups. The hypothesis test findings show significant values of 0.009 < 0.05. The average post-test score in the experimental group was 81.3 > 72.2, which was higher than the pre-test score. It was also discovered that the experimental group's average post-test score was higher than the control group's, with 81.3 > 70.7. Students with this attitude are those who quickly focus on listening to the teacher's explanation and are able to reply to the story.